Efektivitas Shalat Sebagai Rehabilitasi Kesehatan Mental Pada Mahasiswa Bimbingan Penyuluhan Islam UIN Jakarta - Bintang Anugrah; Nasichah Nasichah; Didy Muzaki; Salsabila Salsabila (Lembaga Pengembangan Kinerja Dosen, 2024)
This study discusses the effectiveness of prayer as a method of mental health rehabilitation therapy in college students of UIN Jakarta. Objects of the study are students of Islamic counseling guidance at UIN Jakarta, this study explores the positive impact of prayer on mental well-being, identifying behavioral and psychological changes that occur after the application of this therapy. This research uses qualitative methods through direct interviews. The results provide new insights into the contribution of prayer as a potential rehabilitation tool in the context of higher education, especially in students with mental health challenges.